Peranan Ict Dan Digital Media Dalam Edukasi - Wardana, Agung Kusuma; Handayani, Difha Sulistyawati; Kaunang, Rezha Ribka; Setijadi, Naniek N. (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
In the digital era, technology in education not only broadens access to information but also transforms learning methods. This study evaluates the role of Information and Communication Technology (ICT) and digital media in modern education. Using theories such as Constructivism, Connectivism, and Cognitive Multimedia, along with PRISMA 2020 and Systematic Literature Review (SLR) methods, this research shows that ICT and digital media enhance student engagement and enable innovative teaching methods. However, there are challenges such as limited infrastructure and lack of digital competence. This study suggests investing in technological infrastructure and digital competency training to maximize the potential of ICT. Further research is needed to understand the long-term impacts and to conduct comparative studies between countries. This study provides insights for educators, policymakers, and researchers to develop strategies that support the integration of ICT in education.